COMPLIANCE ANALYSIS OF MEDICAL RECORD FILLING AT KALISAT HOSPITAL JEMBER - Tandy, Dinnya Yesica; Witcahyo, Eri; Utami, Sri (Tadulako University, 2018)
Background & Objective : Hospital quality services is not only from medical services but also the support services, one of them is the completeness of medical records. The medical record filling issues are incompleteness and non-spesific diagnostic writing from the doctor. In 2016, the completeness of medical records in Kalisat Hospital reaches 61,43%. Less motivation and performance may be the cause of doctors and nurses compliance in medical records filling. This study aims to analyze determinants that relate to the compliance of medical records filling in Kalisat Hospital. Material and Method: This study uses descriptive research with a sample size of 47 people. The data is also presented in Scatter diagram to find the correlation of two variables. Result: The result showed that the majority of respondents had good knowledge of medical records, more respondents worked for 5 â€“ 10 years, and majority worked in early adult age 25 - â‰¥ 40 years old. The majority of respondents had a good attitude and motivation. The majority of respondents had a good response about the filling medical records leadership, a good rewards, but a less response about work design in Kalisat Hospital. The scatter diagram showed that there were a positive correlation between knowledge, attitude, motivation, leadership, and rewards variables for the compliance of medical record files. Conclusion: Based on the study, it can be concluded that there is a positive correlation between knowledge, attitude, motivation, leadership, and reward with compliance of medical records file in Kalisat Hospital Jember